2018
DOI: 10.1021/acs.nanolett.8b00458
|View full text |Cite|
|
Sign up to set email alerts
|

Imaging Nanometer Phase Coexistence at Defects During the Insulator–Metal Phase Transformation in VO2 Thin Films by Resonant Soft X-ray Holography

Abstract: We use resonant soft X-ray holography to image the insulator-metal phase transition in vanadium dioxide with element and polarization specificity and nanometer spatial resolution. We observe that nanoscale inhomogeneity in the film results in spatial-dependent transition pathways between the insulating and metallic states. Additional nanoscale phases form in the vicinity of defects which are not apparent in the initial or final states of the system, which would be missed in area-integrated X-ray absorption mea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 25 publications
0
29
1
Order By: Relevance
“…Finally, we note that VO 2 , especially in thin films, can be inhomogeneous, with multiple insulating and metallic phases coexisting in equilibrium [25,[46][47][48]. Therefore, a complete understanding of the phase transition will ultimately need to include how these phases compete dynamically in real space during the light-induced transition [50].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Finally, we note that VO 2 , especially in thin films, can be inhomogeneous, with multiple insulating and metallic phases coexisting in equilibrium [25,[46][47][48]. Therefore, a complete understanding of the phase transition will ultimately need to include how these phases compete dynamically in real space during the light-induced transition [50].…”
Section: Discussionmentioning
confidence: 98%
“…This not only modifies the fluence required to drive the phase transition but can also change the initial phase of the material. Thin films are known to undergo phase separation as a function of temperature [25,[46][47][48]; thus, heating will drive the material away from a purely M 1 initial state. We have shown that there is already a significant volume fraction of a preexisting R phase for high-fluence excitation, but other thermodynamic phases such as M 2 or T [6] could also be present in the sample below our detectable limit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure shows a schematic for such an experiment. We have taken the first step toward such experiments and have recently successfully reconstructed first images during the MIT of VO 2 using the holography with extended reference by autocorrelation linear differential operator reconstruction technique …”
Section: Resultsmentioning
confidence: 99%
“…Such high fluxes have proved sufficient for diffraction-limited holographic imaging in the XUV [37]. Though the flux required to reach the diffraction limit increases as the wavelength decreases, the elemental, bond and magnetic sensitivity of SXR absorption make even nondiffraction limited SXR holography very valuable, for instance in imaging phase co-existence [38]. Holography and other coherent diffraction imaging schemes will be a key application for the next-generation SXR HHG sources.…”
Section: Outlook: Towards Attosecond Soft X-ray Spectroscopymentioning
confidence: 99%